2020
DOI: 10.3390/jcm9103082
|View full text |Cite
|
Sign up to set email alerts
|

Betaglycan Gene (TGFBR3) Polymorphism Is Associated with Increased Risk of Endometrial Cancer

Abstract: We investigated single nucleotide polymorphism (SNP) of the betaglycan gene (TGFBR3) encoding the TGFβ co-receptor in endometrial cancer (EC) and its association with betaglycan expression. The study group included 153 women diagnosed with EC and 248 cancer-free controls. SNP genotyping and gene expression were analyzed using TaqMan probes. Three out of the eight SNPs tested, i.e., rs12566180 (CT; OR = 2.22; 95% CI = 1.15–4.30; p = 0.0177), rs6680463 (GC; OR = 2.34; 95% CI = 1.20–4.53; p = 0.0120) and rs229662… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Although BG has been demonstrated to participate in multiple diseases [17,19,20,32,33] including endometrial cancer [23,33,34], its role in endometriosis is unknown. Thus, we investigated the involvement of BG in endometriosis with endometriotic 12Z cells in vitro, explored the modulation of BG shedding by TGF-β1/-β2, TIMPs and MMPs, and the influence of TGF-βs and BG on wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Although BG has been demonstrated to participate in multiple diseases [17,19,20,32,33] including endometrial cancer [23,33,34], its role in endometriosis is unknown. Thus, we investigated the involvement of BG in endometriosis with endometriotic 12Z cells in vitro, explored the modulation of BG shedding by TGF-β1/-β2, TIMPs and MMPs, and the influence of TGF-βs and BG on wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…An additional mechanism with potential impact on the declined expression of the TGFBR3 gene involves three intronic SNPs, i.e., rs12566180 (c.-114 + 2392C > T) and rs2296621 (c.2285 − 99G > T), which correlate with TGFBR3 transcript loss in endometrial cancer. Moreover, these SNPs and an additional one, rs6680463 (c.-114 + 7008C > G), are significantly associated with increased risk of endometrial cancer, respectively in the case of genotypes CT (rs12566180; OR = 2.22; 95% CI = 1.15-4.30; p = 0.0177), GC (rs6680463; OR = 2.34; 95% CI = 1.20-4.53; p = 0.0120) and TT (rs2296621; OR = 6.40; 95% CI = 1.18-34.84; p = 0.0317) [241] (Table 1). In the context of clinicopathological parameters, only rs2296621 seems to favor an increased tumor aggressiveness evaluated by the WHO grading system (G3 vs. G1/2, GT-OR= 4.04; 95% CI = 1.56-10.51; p = 0.0026; T-OR= 2.38; 95% CI = 1.16-4.85; p = 0.0151).…”
Section: Tgfβ Signal Modulation Can Be Altered By Impaired Co-receptors Expressionmentioning
confidence: 99%
“…The evaluation of betaglycan expression at the transcriptomic level in the context of clinicopathological features of studied material indicates that its loss occurs as an early event in neoplastic transformation of human endometrium [222] (Table 1). Further studies have revealed that observed betaglycan down-regulation results from different genetic mechanisms, including LOH and single nucleotide polymorphisms (SNPs) in the locus of the TGFBR3 gene [240,241]. LOH, assessed using three microsatellite markers (D1S188, D1S435 and D1S1588), is a relatively frequent event and occurs in 52% of all analyzed primary endometrial carcinomas (Table 1).…”
Section: Tgfβ Signal Modulation Can Be Altered By Impaired Co-receptors Expressionmentioning
confidence: 99%
“…[30][31][32][33][34] Allelic loss of TβRIII is a frequent genetic event in many of these cancers, and loss of TβRIII is associated with cancer progression and a poor prognosis. 35,36 Additionally, there are polymorphisms of the TβRIII gene (TGFBR3) associated with increased cancer risk, 37 and multiple microRNAs have been implicated in promoting cancer progression and metastasis via downregulation of TβRIII. [38][39][40][41] The mechanism of action is due in large part to the TβRIII ectodomain shedding from the cell surface, releasing sTβRIII, which antagonizes the tumor-promoting and immunosuppressive effects of TGF-β signaling.…”
Section: Cancermentioning
confidence: 99%